2016
DOI: 10.1002/lary.25960
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medical versus surgical management of peritonsillar abscess: A retrospective observational study

Abstract: 4. Laryngoscope, 126:1529-1534, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 15 publications
4
40
1
Order By: Relevance
“…The mean age in this study was 35.4 years. This agrees with the fact that PTA is common among Adolescents and young adults [9,11]. Risberg and colleagues in a retrospective review over three years in Sweden also had similar mean age (31.2 years) [10].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The mean age in this study was 35.4 years. This agrees with the fact that PTA is common among Adolescents and young adults [9,11]. Risberg and colleagues in a retrospective review over three years in Sweden also had similar mean age (31.2 years) [10].…”
Section: Discussionsupporting
confidence: 81%
“…Majority of our patients (72.2%) were females. This is at variance with what is commonly observed [8,9,11]. Other studies reported no significant difference in the prevalence among males or females [10,25].…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations